Osmanlı Devleti'nde Turizmin Gelişimine Dair Bazı Gözlemler - (:unkn) unknown (My University, 2007)
Turizmin gelişmesi, ulaşım araçlarının bulunabilirliğlinin gelişmesine bağlıdır. Buna bağlı olarak, turizm büyümeye resmen yeni araçların keşfiyle başlamıştır; bu araçların başında tren ve buharla çalışan gemiler gelmektedir. İstanbul’da Avrupa’ya doğrudan bağlantılı ilk tren “Şark Ekspresi” adı altında, ondokuzuncu yüzyılın ilk yarısında açıldı. Ancak, İstanbul’a ilk ziyaretçilerin onsekizinci yüzyılın sonlarına doğru III. Selim zamanında geldiği öğrenilmiştir. Osmanlı Hükümdarlığı, İstanbul’un görmüş olduğu yoğun ilgiden ötürü turistik gezilerin kapasitesini büyütmüş, ayrıca müzelere rehber tahsis ettirmiştir. O zamandan beri İstanbul dünyadaki en ünlü ve en çekici şehirlerden biri olmayı başarmıştır. Özellikle İstanbul’un Avrupa Başkenti seçilmesi sonucu potansiyelini ortaya çıkarmasını ve daha da gelişmesini umuyoruz.

The advancement of tourism is dependent on the development of the availability of transportation. Therefore, the augmentation of tourism officially began with the discovery of vehicles such as steamboats and train. In Istanbul, the first railway with a direct connection to Europe was established in the first half of the 19th century, and it was named “Şark Ekspresi” (The Orient Express). However, it was noticed that the first visitors of Istanbul came in the period of Selim III in the late eighteenth century. Due to the increase of intense attention from the tourists, the Ottoman Empire began to make regulations and arrangements in order to expand the capacity and the quality of the sightseeing areas and started to appoint guides for the museums. Ever since, Istanbul has succeeded to become one of the most famous and intriguing cities in the world. Especially with the positive and propitious effect of having been chosen the European Capital of Culture, it is hoped that Istanbul reveals its immense capacity more and reigns among the best cities of the world as the ancient and most awe-inspiring center of civilization.
Observations on the Development of Tourism in the Ottoman Empire
Keywords: Kültürel Çalışmalar; Tarih